1989
DOI: 10.1002/bem.2250100309
|View full text |Cite
|
Sign up to set email alerts
|

Detection‐threshold of 50‐Hz electric fields by human subjects

Abstract: The threshold intensity for detection of an AC electric field was studied in human subjects at several different temperatures and humidities. The dorsum and palm of the hand were exposed to fields, representing hairy and hairless skin, in order to clarify whether hair movement is critical for field detection. Experiments were carried out on human subjects (seven men and four women) during hot humid weather of July-August and dry cool air of October-November. Threshold values obtained in the summer were 30-65 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
3

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 6 publications
4
30
3
Order By: Relevance
“…Second, an anecdotal report from Cabanes and Gary [1981] indicates that AC field detection is abolished after hair removal. Third, subjects in several studies (AC and DC) referred to a sense of hair movement during field presentation [Cabanes and Gary, 1981;Kato et al, 1989;Blondin et al, 1996]. Finally, Weigel et al [1987] showed that rapidly adapting field receptors [RAF, according to the classification of Burgess et al, 1968] innervating the hairy skin of the cat's paw are activated by AC electric fields.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Second, an anecdotal report from Cabanes and Gary [1981] indicates that AC field detection is abolished after hair removal. Third, subjects in several studies (AC and DC) referred to a sense of hair movement during field presentation [Cabanes and Gary, 1981;Kato et al, 1989;Blondin et al, 1996]. Finally, Weigel et al [1987] showed that rapidly adapting field receptors [RAF, according to the classification of Burgess et al, 1968] innervating the hairy skin of the cat's paw are activated by AC electric fields.…”
Section: Introductionmentioning
confidence: 97%
“…Such systems use either alternating current (AC) or, occasionally, direct current (DC). The electric fields that are generated by the transmission lines can be detected by some individuals [Cabanes and Gary, 1981;Kato et al, 1989;Cohen et al, 1992;Blondin et al, 1996]. To date, it is not clear what factors contribute to the ability of subjects to perceive electric fields.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Stern and Laties Kato et al [1989] and above 10 kV/m by Graham and Cohen 119851, depending on how exposure occurred, highlights both the importance of exposure conditions and how little is known about EF detection by mammals.…”
Section: Discussionmentioning
confidence: 93%
“…*Significant difference between two groups (Paired t-test: P < .05, n ¼ 4). current and indirect stimulation by the perception of extremely low frequency (ELF) field on the body surface have been proposed as possible triggers of the effect of ELF EMF on a living body [Weigel et al, 1987;Kato et al, 1989]. While, magnetic field can generally penetrate the cell membrane, the ELF EF cannot because of the presence of the lipid bilayer (plasma membrane) that functions as an electrical insulator [Poo, 1981;Lee et al, 1993].…”
Section: Discussionmentioning
confidence: 99%